A review on the Current Areas of Geriatric`s Research in Iran - Nematollahi, Shahrzad; Hosseini, Mohammad Ali; Shojaeefar, Ehsan; Aliakbari, Fereshteh; Taheri Tanjani, Parisa (Archives of Men's Health, 2020)
Introduction: Population aging is becoming a global challenge for developing countries. The aim of the present paper is to review the current literature on geriatric health and to propose possible research areas. Methods: By reviewing scientific databases, all published papers in geriatric health within the last 5 years (until 31 December, 2019) were extracted. Inclusion criteria were being about elderly health conducted on Iranian elderly population and published no longer than 5 years ago. Unrelated, foreign studies and qualitative, trend analysis, and case series were excluded. The keywords were classified into 5 macro domain of General, Biological, psychological, Social and Spiritual domains. Results: Until 31 December, 2019, 713 related studies were finally retrieved. 56.8% of keywords belonged to the Biological macro domain. Among which, neurologic disorders had the highest proportion of studies (n=108, 15.1%). The most prevalent subdomain was the “Sociological” (P=15.4%) and the most prevalent keyword was “Quality of life”. The lowest proportion of studies was belonged to Hematology and Otolaryngology (0.4% each). Among the top institutions in terms of publication output are University of Social welfare and Rehabilitation Sciences (11%), Shahid Beheshti University of Medical Sciences (9.7%), and Iran University of Medical Sciences (9%). Conclusion: Most of the literature concerning elderly`s health in Iran has focused on biologic aspect of health. There seems to be an urgent need to develop a research roadmap to cover all aspects of research among elderlies. Various prepositions to develop and promote context-based and innovative strategies are also provided.